Impact of diuresis and number of exchanges on Continuous Ambulatory Peritoneal Dialysis related peritonitis risk in RDPLF registry. - Clément vachey; Caroline Roubiou; Catherine Bresson-Vautrin; Cécile Courivaud (RDPLF, 2020)
Introduction Peritonitis is still a frequent complication among patients undergoing peritoneal dialysis (PD) and it's associated with a significant morbimortality. The aim of our study was to investigate the impact of diuresis volume and number of exchanges (NE) on continuous ambulatory peritoneal dialysis (CAPD) related peritonitis risk. Methods This study was performed with data from the French peritoneal dialysis registry (RDPLF). We included every incident patient in the registry from January 2010 to November 2019 who had at least an adequacy evaluation. Peritonitis risk was assessed firstly by estimating a peritonitis rate per year undergoing PD and secondly by focusing on time to first peritonitis, taking into account competing risks (kidney transplantation, switch to hemodialysis, PD withdrawal whatever the cause or death). Patients whose diuresis was <500mL/24 hours were considered oliguric. Results We included 620 patients in our analysis. The mean age was 72,9 (standard deviation (SD)=15,1). Two hundred and six (39,55%) had at least one peritonitis episode. No difference was observed between oliguric patients and the others. However, we noticed an increased risk in patients with a NE≥22 per week (HR=1,55, P=0,0005 and HR=1,47, P=0,02 considering competing risks). We also observed a lower risk in diabetic patients HR=0,74, p=0,02 and HR=0,77, p=0,0497). Conclusion We didn't find any impact of diuresis volume on peritonitis risk. Whereas, the NE seems to be a considerable risk factor, especially when it's superior to 22 per week.